Constructing Digital Sovereignty in Russian and Chinese Media: Big Data Analysis - Evgeniya V. Popova; Olga V. Ustyuzhantseva; Haoyue Gao (Vestnik RUDN. International Relations, 2025)
This study explores the formation of the concept of digital sovereignty in non-liberal democratic countries through a comparative analysis of media discourses in Russia and China. Against the backdrop of intensifying global competition and technological transformations associated with the Fourth Industrial Revolution, comparing how different actors in non-democratic states construct digital sovereignty becomes crucial for understanding the divergences between the two countries. The research methodology is based on big data analysis of media publications, employing automated text analysis methods ( PolyAnalyst ). The sample includes over 2,800 materials from Russian and Chinese media outlets covering the period from 2011 to 2021. The analysis was conducted across several dimensions: economic and political content, national and international levels, and the technologies incorporated into the concept of digital sovereignty. The study adopts a constructivist approach, viewing digital sovereignty as a phenomenon discursively constructed by various actors. Particular attention was given to mapping actor networks and identifying dominant thematic clusters. The scientific novelty of the research lies in its comparative approach to studying digital sovereignty in non-liberal democracy countries. The study demonstrates that digital sovereignty is not a monolithic concept: its understanding in Russia and China differs significantly. In Russia, narratives of national security, state control, and protectionism prevail, whereas in China, the emphasis is placed on technological development, economic leadership, and global competitiveness. Furthermore, the study reveals the different roles played by economic actors and technological imaginaries in shaping the concepts of digital sovereignty. The findings show that Russia and China employ distinct strategies and narratives to legitimize digital sovereignty. This work contributes to the understanding of the role of media in shaping sovereignty concepts and opens up new avenues for further research in the fields of digital governance and international relations.